Rationality and discernment: a philosophical-legal debate on the alteration of criteria for the definition of civil capacity (2018)
Based on the analysis of the different philosophical currents, this text discusses the concept of autonomy in the case of complex legal conflicts, as in the definition of civil capacity, due to the recent entry into force of Law no. 13,146/15 (Statute of the Person with Deficiency) in the Brazilian legal system. There is debate on the measure of establishing aprioristic limits to an exercise of intersubjective freedom and on how sufficient reasons should be offered to the restriction of any and all freedom. At the same time, there is the concernto make the autonomy of the person powerful, as a relevant principle for the construction of morality in contemporary society. This allows the questioning of the recent approval of the Statute of the person with deficiency in Brazil, by suppressing the paragraphs of art. 3 of the Brazilian Civil Code, extirpating, normatively, the criterion of discernment for the determination of civil capacity. Based on the juridical discourse, the rescue of the concept of discernment for the promotion of the free development of the human personality is pointed out as fundamental, for purposes of interpretation.